2021
DOI: 10.3171/case21207
|View full text |Cite
|
Sign up to set email alerts
|

L5 nerve root injury caused by anterolateral malpositioning of loosened S1 pedicle screws: illustrative cases

Abstract: BACKGROUND Although malpositioning of pedicle screws into the spinal canal and intervertebral foramen can cause spinal nerve root injuries, there are few reports of L5 nerve root injuries when S1 pedicle screws have been inserted anterolaterally. The authors report two cases of L5 nerve root injury caused by anterolateral malpositioning of loosened S1 pedicle screws. OBSERVATIONS In both patients, S1 pedicle screws were inserted toward the outside of the S1 anterior foramen, and the tip of the screws perfora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Some reports have also focused on the complications of L5 nerve root injury caused by anterolateral misplacement of the S1 pedicle screws. [22][23][24] Sacral screw fixation is the gold standard for sacral bone purchase. The two most commonly used methods of screw insertion are into the promontory through the S1 pedicle with an anteromedial orientation and into the ala of the sacrum with an anterolateral orientation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some reports have also focused on the complications of L5 nerve root injury caused by anterolateral misplacement of the S1 pedicle screws. [22][23][24] Sacral screw fixation is the gold standard for sacral bone purchase. The two most commonly used methods of screw insertion are into the promontory through the S1 pedicle with an anteromedial orientation and into the ala of the sacrum with an anterolateral orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inserting the S1 pedicle screws medially with an angle > 0° toward the inside of the S1 anterior foramina can help avoid injury of the L5 nerve root. Previously, Tamagawa et al 24 reported 2 cases of L5 nerve root injury due to anterolateral misplacement of the S1 pedicle screws. In those cases, as the S1 pedicle screws were inserted outside of the S1 anterior foramina over bicortical fixation, the L5 nerve roots were stimulated by the screw tips.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outlet views of the S1 and S2 segments can be obtained with the beam parallel to the "tunnels" of each pair of neural foramina and help the surgeon avoid iatrogenic violation of the foramina by clearly defining these structures. [13][14][15] "Optimal" outlet views perfectly aligned by these definitions may be difficult to achieve in patients with large body habitus or anteverted pelves with increased pelvic incidence because the necessary caudal tilt of the C-arm gantry is not possible due to collision of the C-arm radiation source and detector with the undersurface of the radiolucent operating table and the thighs of the patient, respectively. Suboptimal fluoroscopic views of the upper sacral neural foramen can lead to the misinterpretation of the position of instruments and implants relative to osseous and neurovascular structures and subsequently increase the risk of iatrogenic complications.…”
Section: Introductionmentioning
confidence: 99%